Cross-Region Transfers in a Monetary Union : Evidence from the US and Some Implications - Pennings, Steven (World Bank, Washington, DC, 2020)
US federal transfers to individuals are large, countercyclical, vary geographically, and are often credited for helping stabilize regional economies. This paper estimates the short-run effects of these transfers using plausibly exogenous regional variation in temporary stimulus packages and earlier permanent Social Security increases. States that received larger transfers tended to grow faster contemporaneously, with a multiplier of around 1.5 for permanent transfers and 1/3 for temporary transfers. Results are broadly consistent with an open-economy New Keynesian model. At business-cycle frequencies, cross-region transfer multipliers are not large, suggesting only modest gains in regional stabilization from US federal automatic stabilizers.